Porous silicon electrode active material particle and method for manufacturing the same, electrode mixture, battery
Patent Information
- Application Number
- CN202610226999.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-24
- Filing Date
- 2026-02-26
- Publication Date
- 2026-10-27
AI Technical Summary
[0038]根据本公开,能够提供膨胀收缩得到抑制的多孔硅电极活性物质粒子及其制造方法、包含这样的多孔硅电极活性物质粒子的电极合材和包含这样的电极合材的电池。
Smart Images

Figure CN122992049A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to porous silicon electrode active material particles and methods for manufacturing the same, electrode composites, and batteries. Background Technology
[0002] As disclosed in Patent Document 1, batteries containing porous silicon particles are known as negative electrode active materials.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-170605 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] In batteries containing silicon as the negative electrode active material, silicon sometimes expands and contracts during charging and discharging. Although porous silicon particles can absorb this expansion and contraction due to their fine pores, there is room for further improvement in suppressing such expansion and contraction.
[0008] The purpose of this disclosure is to provide porous silicon electrode active material particles with suppressed expansion and contraction, a method for manufacturing the same, an electrode assembly containing such porous silicon electrode active material particles, and a battery containing such an electrode assembly.
[0009] Methods for solving problems
[0010] The author of this application has discovered that the above-mentioned problem can be solved by using the following methods.
[0011] <Option 1>
[0012] Porous silicon electrode active material particles having multiple pores and pillars of a three-dimensional structure surrounding the multiple pores, and the ratio of the average pore diameter to the average pillar diameter is 8.0 or less.
[0013] <Option 2>
[0014] According to Scheme 1, the proportion of porous silicon electrode active material particles is 2.0 or more and 7.5 or less.
[0015] <Option 3>
[0016] According to Scheme 2, the proportion of porous silicon electrode active material particles is 3.0 or more and 6.5 or less.
[0017] <Option 4>
[0018] The porous silicon electrode active material particles according to any one of Schemes 1 to 3, wherein the average pore diameter is 20 nm or more and 35 nm or less.
[0019] <Option 5>
[0020] The porous silicon electrode active material particles according to any one of Schemes 1 to 4, wherein the average pillar diameter is more than 1 nm and less than 15 nm.
[0021] <Option 6>
[0022] The porous silicon electrode active material particles according to any one of Schemes 1 to 5, wherein the porosity based on the cross-sectional SEM image is 30% or more and 55% or less.
[0023] <Option 7>
[0024] The electrode material comprises porous silicon electrode active material particles according to any one of embodiments 1 to 6.
[0025] <Option 8>
[0026] The battery has, in sequence, a negative electrode active material layer, an electrolyte layer, and a positive electrode active material layer, wherein the negative electrode active material layer comprises the electrode composite material according to embodiment 7.
[0027] <Option 9>
[0028] The battery according to Scheme 8 is a solid battery in which the electrolyte layer contains a solid electrolyte.
[0029] <Option 10>
[0030] The method for manufacturing porous silicon electrode active material particles according to any one of Schemes 1 to 6 includes the following steps:
[0031] (a) Reduction treatment of silica particles with magnesium at a temperature above 700°C and below 750°C yields precursor particles containing silicon and magnesium oxide; and
[0032] (b) Remove the magnesium oxide from the precursor particles.
[0033] <Option 11>
[0034] According to the method of Scheme 10, in step (a), the reduction treatment of the silicon dioxide particles with the magnesium lasts for more than 10 hours and less than 20 hours.
[0035] <Option 12>
[0036] According to the method of scheme 10 or 11, in step (b), the magnesium oxide is removed by treating the precursor particles with acid.
[0037] Invention Effects
[0038] According to this disclosure, it is possible to provide porous silicon electrode active material particles whose expansion and contraction are suppressed, a method for manufacturing the same, an electrode assembly containing such porous silicon electrode active material particles, and a battery containing such an electrode assembly. Attached Figure Description
[0039] Figure 1 A schematic cross-sectional view is shown for illustrating an example of the battery of this disclosure.
[0040] Figure 2 The image shows a cross-sectional SEM image of an electrode active material layer containing porous silicon electrode active material particles based on Example 1, with the fine pore portion represented in white and the support portion in black.
[0041] Figure 3 A graph showing the relationship between the average pore diameter / average support diameter of the batteries in Examples 1-4 and Comparative Example 1 and the increase in constraint pressure.
[0042] Explanation of reference numerals in the attached figures
[0043] 1 Battery
[0044] 10 Negative current collector layer
[0045] 20 Negative electrode active material layer
[0046] 30 Electrolyte layer
[0047] 40 Positive electrode active material layer
[0048] 50 Positive current collector layer Detailed Implementation
[0049] The embodiments of this disclosure will now be described in detail. Furthermore, this disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the disclosure's intent.
[0050] <<Porous Silicon Electrode Active Material Particles>>
[0051] The porous silicon electrode active material particles disclosed herein have multiple pores and support pillars forming a three-dimensional structure surrounding the multiple pores. In the porous silicon electrode active material particles of this disclosure, the ratio of the average pore diameter to the average support pillar diameter is 8.0 or less.
[0052] The present applicant has discovered porous silicon electrode active material particles with multiple pores and a three-dimensional structure surrounding the pores, and with a relatively small ratio of the average pore diameter to the average pillar diameter, which can suppress the expansion and contraction of silicon during battery charging and discharging. The reason for this is not intended to be based on any theoretical constraints, but is conjectured as follows: For example, in solid-state batteries, during the molding of the electrode active material layer, pressing is sometimes performed for densification, etc. It is believed that the porous silicon electrode active material particles of this disclosure are not easily plastically deformed by such pressing or other stresses, and therefore, the pores of the porous silicon electrode active material particles are less likely to be crushed or collapse. Therefore, it is believed that the pores of the porous silicon electrode active material particles can absorb the expansion and contraction of the pillars composed mainly of silicon.
[0053] In this disclosure, the term "pillar" refers to the portion of a porous silicon electrode active material particle other than its pores. The presence of pillars and pores can be confirmed, for example, by observing the cross-section of the porous silicon electrode active material particle using a scanning electron microscope (SEM).
[0054] "Electrode active material" can be either "positive electrode active material" or "negative electrode active material", and in particular, it can be "negative electrode active material".
[0055] The elements constituting the porous silicon electrode active material particles of this disclosure will be described below.
[0056] <Fine pores>
[0057] The porous silicon electrode active material particles disclosed herein have multiple micropores. These micropores are capable of absorbing the expansion and contraction of the silicon-containing support structure.
[0058] (Average pore diameter)
[0059] The porous silicon electrode active material particles disclosed herein have an average pore diameter of 10 nm or more, 15 nm or more, 20 nm or more, 21 nm or more, 22 nm or more, 23 nm or more, or 24 nm or more; alternatively, they can be 50 nm or less, 40 nm or less, 35 nm or less, 32 nm or less, 30 nm or less, 28 nm or less, 26 nm or less, or 25 nm or less. The average pore diameter can be 15 nm or more and 40 nm or less, 20 nm or more and 35 nm or less, or 22 nm or more and 32 nm or less. Therefore, the pores can effectively absorb the expansion and contraction of the support.
[0060] There are no particular limitations on the method for determining the average pore diameter; for example, it can be determined as follows: First, a cross-sectional SEM image is obtained by processing the cross-section of the negative electrode active material layer using a cross-sectional polishing method. The accelerating voltage for obtaining the cross-sectional SEM image can be 2kV. Second, the obtained cross-sectional SEM image is binarized using image processing software Image-J (Ver. 1.52), separating it into black pillar regions and white pore regions. In the cross-sectional SEM image before image processing, the outermost layer is the pores, and the second and subsequent layers are pillars; therefore, the areas represented in gray are made white pore regions. Furthermore, the average pore diameter can be determined using the functions of Image-J.
[0061] (Porosity)
[0062] In the porous silicon electrode active material particles disclosed herein, the porosity based on cross-sectional SEM images can be 30% or more, 35% or more, 40% or more, 45% or more, or 50% or more, or it can be less than 57%, less than 56%, or less than 55%. This porosity can be 30% or more and less than 55%, 35% or more and less than 55%, or 40% or more and less than 55%. Therefore, the fine pores can effectively absorb the expansion and contraction of the support.
[0063] There are no particular limitations on the method for measuring porosity. For example, it can be calculated as the proportion of the area of the white portion in the image described above, which is a cross-sectional SEM image processed using Image-J image processing. Furthermore, the porosity can be calculated as "the area of the entire image (100 area%) - porosity".
[0064] (Number of pores)
[0065] Regarding the number of pores, there are no particular limitations as long as the average pore diameter and porosity are within the ranges mentioned above.
[0066] <Pillar>
[0067] The porous silicon electrode active material particles disclosed herein have a three-dimensional structure with supports surrounding multiple micropores. The silicon contained in the supports expands and contracts during the charging and discharging of the battery. Such expansion and contraction can be absorbed by the aforementioned micropores.
[0068] The support may contain elements or compounds other than silicon, or it may not contain them. Examples of elements or compounds other than silicon include lithium and magnesium oxide, which may remain after the manufacturing of porous silicon electrode active material particles. Details of the manufacturing method for porous silicon electrode active material particles will be described later.
[0069] (Average support diameter)
[0070] In the porous silicon electrode active material particles disclosed herein, the average pillar diameter can be 1 nm or more, 3 nm or more, or 4 nm or more, and can also be 15 nm or less, 13 nm or less, 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, or 5 nm or less. The average pillar diameter can be 1 nm or more and 15 nm or less, 3 nm or more and 13 nm or less, or 4 nm or more and 7 nm or less. Therefore, the fine pores can effectively absorb the expansion and contraction of the pillars.
[0071] There is no particular limitation on the method for determining the average diameter of the support column. For example, by processing the cross-sectional SEM image with the image processing software Image-J (Ver.1.52), and then processing the above image with the porous body image analysis library PoreSpy (Ver.2.4.1) in Python (registered trademark), it is possible to fit (approximate) a sphere inside the support column and calculate it as a weighted average of the diameters of multiple spheres.
[0072] (Average pore diameter / Average support diameter)
[0073] In the porous silicon electrode active material particles disclosed herein, the ratio of the average pore diameter to the average pillar diameter is 8.0 or less. Therefore, the pores can absorb the expansion and contraction of the pillars.
[0074] This ratio can be 1.5 or higher, 2.0 or higher, or 2.5 or higher; alternatively, it can be 7.5 or lower, or 7.0 or lower. The ratio can also be 2.0 or higher and 7.5 or lower. Therefore, the fine pores can effectively absorb the expansion and contraction of the support.
[0075] Specifically, this ratio can be 3.0 or higher, 3.5 or higher, 4.0 or higher, 4.5 or higher, 5.0 or higher, or 5.5 or higher; alternatively, it can be 6.5 or lower, or 6.0 or lower. This ratio can be 3.0 or higher and 6.5 or lower. Thus, the fine pores can effectively absorb the expansion and contraction of the support. The reason for this is not intended to be bound by any theory, but it is believed that by ensuring the pore diameter is not too small relative to the support diameter—that is, by ensuring it is of a suitable size—the absorption efficiency of the support's expansion and contraction by the fine pores is improved.
[0076] In the porous silicon electrode active material particles disclosed herein, the ratio of (average pore diameter × porosity) to (average pillar diameter × pillar ratio) can be 2.0 or more, 3.0 or more, 4.0 or more, 5.0 or more, 6.0 or more, or 6.5 or more; alternatively, it can be 10.0 or less, 9.0 or less, 8.5 or less, 8.0 or less, 7.5 or less, or 7.0 or less. Therefore, the pores can effectively absorb the expansion and contraction of the pillars.
[0077] <<Method for Manufacturing Porous Silicon Electrode Active Material Particles>>
[0078] The method of this disclosure for manufacturing porous silicon electrode active material particles includes the following steps:
[0079] (a) Reduction treatment of silica particles with magnesium at a temperature above 700°C and below 750°C yields precursor particles containing silicon and magnesium oxide; and
[0080] (b) Remove magnesium oxide from the precursor particles.
[0081] <Preparation of Precursor Particles>
[0082] The method disclosed herein includes (a) reducing silica particles with magnesium at a temperature of 700°C or higher and 750°C to obtain precursor particles containing silicon and magnesium oxide. By controlling the temperature during the reduction process, the pore diameter, support diameter, and porosity can be adjusted.
[0083] In the method disclosed herein, in step (a), the silica particles are reduced with magnesium for a period of 10 to 20 hours. By controlling the reduction treatment time in this way, the pore diameter, support diameter, and porosity can be adjusted.
[0084] There are no particular limitations on the method for reducing silica particles with magnesium; for example, a method of contacting silica particles with magnesium vapor can be cited. There are also no particular limitations on the method for generating magnesium vapor; for example, a method of heating a reducing agent, such as a magnesium alloy or metallic magnesium, as a magnesium source can be cited. Specifically, a method for reducing silica particles with magnesium can be exemplified by heating silica particles and magnesium in the same system at a temperature above the temperature at which magnesium vapor is generated.
[0085] There are no particular limitations on the magnesium alloy; for example, it can be at least one selected from Mg2Si, MgCa, MgCu2, MgNi2, and MgSn.
[0086] In the method of contacting silica particles with magnesium vapor, there is no particular limitation on the pressure at which the silica particles are reduced with magnesium. This pressure may be, for example, less than one atmosphere, less than 100 Pa, or less than 20 Pa. In addition, this pressure may be the Mg vapor pressure below the equilibrium pressure of the following reaction formula (1).
[0087] [Chemistry 1]
[0088]
[0089] <Removal of magnesium oxide>
[0090] The method of this disclosure includes (b) removing magnesium oxide from the precursor particles. This forms fine pores in the portion where magnesium oxide has been removed from the precursor particles. In the method of this disclosure, at least a portion of the magnesium oxide may be removed, or all of it may be removed.
[0091] In the method of this disclosure, in step (b), magnesium oxide can be removed by treating the precursor particles with acid.
[0092] As an acid, there are no particular limitations; for example, inorganic acids such as hydrochloric acid, nitric acid, and sulfuric acid can be listed.
[0093] There are no particular restrictions on the pH of the acid; for example, it can be below 3, below 2, or below 1.
[0094] There is no particular limitation on the molar ratio of magnesium oxide to acid; for example, it can be 1:5 to 1:10.
[0095] Specifically, magnesium oxide can be removed by using the following steps:
[0096] Prepare a specified amount of precursor particles and a specified amount of 7% hydrochloric acid solution in an environment with an oxygen concentration of less than 5%.
[0097] Add the precursor particles to a beaker containing hydrochloric acid solution and stir at room temperature for 1 hour.
[0098] Place the hydrochloric acid solution containing the precursor particles into a suction flask and filter.
[0099] The filtered powder is then rinsed with water.
[0100] Pour ethanol, then rinse with water;
[0101] Transfer the filtered powder to a SUS dish;
[0102] Place the SUS dish into a laminated bag, zip the bag up, and remove the bag from an environment with an oxygen concentration below 5%; then,
[0103] In an environment with an oxygen concentration of less than 5% equipped with a dryer, use the dryer to dry at 120°C for 12 hours.
[0104] In this way, by controlling the acid treatment conditions during magnesium oxide removal, especially by performing acid treatment in an environment with an oxygen concentration of less than 5%, it is possible to adjust the pore diameter, support diameter, and porosity.
[0105] The porous silicon electrode active material particles disclosed herein can also be manufactured using methods other than those described above. One such method is illustrated below: First, silicon and lithium metal are mixed to prepare LiSi precursor particles. Next, the LiSi precursor particles are mixed with a dispersion medium. The resulting LiSi precursor particle dispersion is reacted with ethanol, which serves as a Li extraction solvent, and then with acetic acid. In this way, Li is removed from the precursor particles, thereby obtaining porous silicon electrode active material particles with fine pores.
[0106] <<Electrode Composite Material>>
[0107] The electrode assembly disclosed herein comprises porous silicon electrode active material particles. The electrode assembly may optionally contain solid electrolytes, conductive additives, binders, etc.
[0108] Regarding this disclosure, "electrode composite" means a composition capable of forming an electrode active material layer, either as is or by further containing other components. Additionally, regarding this disclosure, "electrode composite slurry" means a slurry that, in addition to the "electrode composite," includes a dispersion medium, thereby being coated and dried to form an electrode active material layer.
[0109] Regarding this disclosure, "electrode composite" can be "positive electrode composite" or "negative electrode composite", and in particular, it can be "negative electrode composite".
[0110] The elements constituting the electrode composite of this disclosure will be described below.
[0111] <Porous silicon electrode active material particles>
[0112] For porous silicon electrode active material particles, please refer to the above description.
[0113] There is no particular limitation on the content of porous silicon electrode active material particles in the electrode composite material; it can be appropriately set considering the desired battery capacity, etc.
[0114] <Solid Electrolytes>
[0115] Examples of solid electrolytes include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes, as well as organic polymer electrolytes such as polymer electrolytes. Sulfide solid electrolytes are particularly noteworthy.
[0116] For example, in the case of a lithium-ion secondary battery, the solid electrolyte can have lithium-ion conductivity.
[0117] Examples of sulfide solid electrolytes with lithium-ion conductivity include those containing Li, X (where X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. Furthermore, sulfide solid electrolytes may further contain at least one of O and a halogen element. Examples of halogen elements include F, Cl, Br, and I.
[0118] Examples of sulfide solid electrolytes include Li₂S-P₂S₅, Li₂S-P₂S₅-LiI, Li₂S-P₂S₅-GeS₂, Li₂S-P₂S₅-Li₂O, Li₂S-P₂S₅-Li₂O-LiI, Li₂S-P₂S₅-LiI-LiBr, Li₂S-SiS₂, Li₂S-SiS₂-LiI, Li₂S-SiS₂-LiBr, Li₂S-SiS₂-LiCl, Li₂S-SiS₂-B₂S₃-LiI, Li₂S-SiS₂-P₂S₅-LiI, Li₂S-B₂S₃, Li₂S-P₂S₅-ZmSn (where m and n are positive numbers, and Z is any one of Ge, Zn, or Ga), Li₂S-GeS₂, Li₂S-SiS₂-Li₃PO₄, and Li₂S-SiS₂-Li x MO y (Where x and y are positive numbers. M is any one of P, Si, Ge, B, Al, Ga, and In).
[0119] As an oxide solid electrolyte with lithium-ion conductivity, examples include solid electrolytes containing Li, Y (where Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. A specific example is Li7La3Zr2O. 12 Li 7-x La3 (Zr) 2-x Nb x O 12 (0≤x≤2), Li5La3Nb2O 12 Garnet-type solid electrolytes; perovskite-type solid electrolytes such as (Li,La)TiO3, (Li,La)NbO3, and (Li,Sr)(Ta,Zr)O3; NASICON-type solid electrolytes such as Li(Al,Ti)(PO4)3 and Li(Al,Ga)(PO4)3; Li-PO solid electrolytes such as Li3PO4 and LIPON (a compound in which part of the O in Li3PO4 is replaced by N); and Li-BO solid electrolytes such as Li3BO3 and a compound in which part of the O in Li3BO3 is replaced by C.
[0120] There are no particular limitations on the content of solid electrolyte in the electrode material; it can be set appropriately, taking into account desired ion conductivity, etc.
[0121] <Conductive additives>
[0122] Conductive additives may be, for example, carbon materials, metal particles, or combinations thereof. Carbon materials may be, for example, non-fibrous carbon materials such as acetylene black (AB) and Ketjen black (KB); fibrous carbon materials such as vapor-grown carbon fibers (VGCF), carbon nanotubes (CNT), and carbon nanofibers (CNF), or combinations thereof. Metal particles may be, for example, nickel, copper, iron, stainless steel, or combinations thereof.
[0123] There are no particular limitations on the content of conductive additives in the electrode composite material; it can be set appropriately by taking into account desired conductivity, etc.
[0124] <Adhesive>
[0125] The adhesives may be, for example, rubber-based adhesives such as butadiene rubber, hydrogenated butadiene rubber, styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, acrylate butadiene rubber (ABR), and ethylene-propylene rubber; fluorinated adhesives such as polyvinylidene fluoride (PVdF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVdF-HFP), polytetrafluoroethylene, and fluororubber; polyolefin thermoplastic resins such as polyethylene, polypropylene, and polystyrene; imide resins such as polyimide and polyamide-imide; amide resins such as polyamide; acrylic resins such as polymethyl acrylate and polyethyl acrylate; methacrylic resins such as polymethyl methacrylate and polyethyl methacrylate; or combinations thereof.
[0126] There is no particular limitation on the content of adhesive in the electrode assembly; it can be set appropriately, taking into account desired adhesion and other factors.
[0127] <Other Ingredients>
[0128] The electrode material may further include components other than those mentioned above, or it may not contain any of them.
[0129] <<Battery>>
[0130] The battery disclosed herein sequentially comprises a negative electrode active material layer, an electrolyte layer, and a positive electrode active material layer, wherein the negative electrode active material layer contains the electrode composite material of this disclosure. That is, in the battery of this disclosure, the electrode composite material of this disclosure is used as the negative electrode composite material. Figure 1 As illustrated, the battery 1 of this disclosure may sequentially have a negative current collector layer 10, a negative active material layer 20 containing the electrode composite of this disclosure, an electrolyte layer 30, a positive active material layer 40, and a positive current collector layer 50.
[0131] The battery disclosed herein can be a liquid-based battery or a solid-state battery, particularly a solid-state battery. Regarding this disclosure, "solid-state battery" means a battery that contains at least a solid electrolyte as an electrolyte; therefore, a solid-state battery can contain a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. Additionally, a solid-state battery can be an all-solid-state battery, that is, a battery that contains only a solid electrolyte as an electrolyte.
[0132] The battery disclosed herein can be a secondary battery, and in particular a lithium-ion secondary battery.
[0133] With respect to the battery disclosed herein, it can be constrained from both sides of the stacking direction of the aforementioned layers by means of constraint members such as end plates. As a constraint method, methods such as using the constraint torque of bolts can be exemplified, but it is not limited to this.
[0134] The elements constituting the battery of this disclosure will now be described. Hereinafter, examples will be provided for the case where the battery of this disclosure is an all-solid-state battery.
[0135] <Negative current collector layer>
[0136] The negative electrode current collector layer can be in the form of foil, plate, screen, perforated metal, foam, etc. It can be a metal foil or metal screen, or a carbon sheet, but particularly a metal foil. The negative electrode current collector layer can be composed of multiple foils or sheets.
[0137] There are no particular limitations on the metal constituting the negative electrode current collector layer; for example, it can be copper, nickel, chromium, gold, platinum, silver, aluminum, iron, titanium, zinc, cobalt, stainless steel, etc. In particular, the negative electrode current collector layer may contain at least one metal selected from copper, nickel, and stainless steel.
[0138] To adjust resistance, etc., a coating may be formed on the surface of the negative current collector layer. Furthermore, the negative current collector layer may be a metal foil or a layer formed by depositing or vapor-depositing the aforementioned metal onto a substrate. Additionally, when the negative current collector layer is composed of multiple metal foils, layers may be present between these multiple metal foils.
[0139] There is no particular limitation on the thickness of the negative electrode current collector layer. For example, it can be 0.1 μm or more, or 1 μm or more. Alternatively, it can be less than 1 mm or less than 100 μm.
[0140] <Negative Electrode Active Material Layer>
[0141] The negative electrode active material layer comprises the electrode assembly of this disclosure. The electrode assembly of this disclosure can be referred to the above description. The negative electrode active material layer can be formed into a layered structure by the electrode assembly of this disclosure itself.
[0142] There is no particular limitation on the thickness of the negative electrode active material layer; for example, it can be above 0.1 μm and below 1000 μm.
[0143] <Solid Electrolyte Layer>
[0144] The solid electrolyte layer contains at least solid electrolyte particles and may further include adhesives, etc.
[0145] For solid electrolyte particles and binders, please refer to the above description.
[0146] There is no particular limitation on the thickness of the solid electrolyte layer; for example, it can be greater than 0.1 μm and less than 1000 μm.
[0147] <Positive Electrode Active Material Layer>
[0148] The positive electrode active material layer contains at least a positive electrode active material, and may further include solid electrolyte, conductive additives, binders, etc.
[0149] There are no particular limitations on the positive electrode active material; for example, it can be an oxide active material. Oxide active materials used in lithium-ion batteries can include, for example, LiCoO2, LiMnO2, Li2NiMn3O8, LiVO2, LiCrO2, LiFePO4, LiCoPO4, LiNiO2, and LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc. Additionally, coatings containing Li ion-conducting oxides such as LiNbO3 can be formed on the surface of these active materials.
[0150] There is no particular limitation on the content of positive electrode active material in the positive electrode active material layer.
[0151] For solid electrolytes, conductive additives, and adhesives, please refer to the above description.
[0152] There is no particular limitation on the thickness of the positive electrode active material layer; for example, it can be above 0.1 μm and below 1000 μm.
[0153] <Positive current collector layer>
[0154] The positive current collector layer can be in the form of foil, plate, screen, perforated metal, foam, etc. The positive current collector layer can be a metal foil or a metal screen, and particularly a metal foil. The positive current collector layer can be composed of multiple foils.
[0155] The metals constituting the positive current collector layer can be copper, nickel, chromium, gold, platinum, silver, aluminum, iron, titanium, zinc, cobalt, stainless steel, etc. In particular, the positive current collector layer may contain aluminum.
[0156] To adjust resistance, etc., a coating may be formed on the surface of the positive current collector layer. Alternatively, the positive current collector layer may be a metal foil or a layer formed by depositing or vapor-depositing the aforementioned metal onto a substrate. Furthermore, when the positive current collector layer is composed of multiple metal foils, layers may be formed between these multiple metal foils.
[0157] There is no particular limitation on the thickness of the positive electrode current collector layer. For example, it can be 0.1 μm or more, or 1 μm or more, or less than 1 mm, or less than 100 μm.
[0158] <Other Components>
[0159] The battery can be a battery in which the above-described components are housed within an outer casing. Regarding the outer casing, any known outer casing for the battery can be used. Furthermore, multiple batteries can be arbitrarily electrically connected and stacked to form a battery pack. In this case, the battery pack can be housed within a known battery casing. In addition to these features, the battery can include obvious components such as necessary terminals. The battery shape can be, for example, coin-shaped, stacked (bag-shaped), cylindrical, square, etc.
[0160] There are no particular limitations on the method of manufacturing the battery disclosed herein, such as including forming a negative electrode active material layer containing the electrode composite of the present disclosure.
[0161] As a method for forming a negative electrode active material layer containing an electrode composite, an example is a method of mixing constituent materials such as porous silicon electrode active material particles to obtain an electrode composite, and then dry-forming or wet-forming the obtained electrode composite.
[0162] The method of manufacturing the battery disclosed herein may further include: sequentially stacking a negative electrode current collector layer, a negative electrode active material layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer to form an electrode stack.
[0163] In the electrode stack, terminals and other components are installed as needed. The battery is obtained by housing the electrode stack within a battery casing and sealing it.
[0164] [Example]
[0165] <<Example 1>>
[0166] <Preparation of Porous Silicon Electrode Active Material Particles>
[0167] (Preparation of precursor particles)
[0168] Silica particles and magnesium (Mg) were calcined together in the same system at 700°C for 10 hours. The silica particles were then reduced with Mg to obtain precursor particles containing silicon (Si) and magnesium oxide (MgO).
[0169] (Removal of magnesium oxide)
[0170] The precursor particles were treated with hydrochloric acid at pH 1 to dissolve and remove MgO. Specifically, the following steps were used to remove MgO:
[0171] Prepare 1g of precursor particles and 75.64ml of 7% hydrochloric acid solution in an environment with an oxygen concentration of less than 5%.
[0172] Add the precursor particles to a beaker containing hydrochloric acid solution and stir at room temperature for 1 hour.
[0173] Place the hydrochloric acid solution containing the precursor particles into a suction flask and filter.
[0174] The filtered powder is rinsed with water.
[0175] Pour ethanol, then rinse with water;
[0176] Transfer the filtered powder to a SUS dish;
[0177] Place the SUS dish into a laminated bag, zip the bag up, and remove the bag from an environment with an oxygen concentration below 5%; then,
[0178] In an environment with an oxygen concentration of less than 5% equipped with a dryer, use the dryer to dry at 120°C for 12 hours.
[0179] This creates fine pores in Si, resulting in porous silicon electrode active material particles. Furthermore, the molar ratio of MgO to hydrochloric acid is 1:10.
[0180] <Fabrication of the Negative Electrode Active Material Layer>
[0181] Porous silicon electrode active material particles, serving as the negative electrode active material, and a sulfide solid electrolyte (volume ratio 100:80) are added to a dispersion medium and mixed using an ultrasonic homogenizer to obtain a negative electrode composite slurry. The obtained slurry is then coated onto a copper foil serving as the negative electrode current collector layer using a doctor blade. The dispersion medium is then dried and removed to obtain a coated film. The coated film is densified by pressing to obtain a negative electrode laminate with a negative electrode active material layer formed on the negative electrode current collector layer.
[0182] <Calculation of average aperture diameter and average support diameter>
[0183] For the cross-section formed by processing the negative electrode active material layer using the cross-section polishing method, a cross-sectional SEM image was obtained. The accelerating voltage for obtaining the cross-sectional SEM image was 2kV.
[0184] The obtained cross-sectional SEM image was binarized using Image-J (Ver. 1.52) image processing software, separating it into black pillar regions and white pore regions. In the original cross-sectional SEM image, the outermost layer represents pores, and the subsequent layers represent pillars; therefore, areas represented in gray were made white pore regions. The resulting image is shown below. Figure 2 The average pore diameter was determined using Image-J, and the porosity was calculated as the proportion of the white portion in the Image-J processed image. Furthermore, the Image-J processed image was processed using the Python (trademarked) porous body image analysis library PoreSpy (Ver. 2.4.1) to fit spheres inside the support structure, and the weighted average of the diameters of multiple spheres was calculated as the average support structure diameter.
[0185] <Fabrication of the Positive Electrode Active Material Layer>
[0186] LiNi will be used as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2 surface-treated with lithium niobate (LiNbO3), a sulfide solid electrolyte, VGCF (manufactured by Resonac Co., Ltd.) as a conductive additive, and PVdF (manufactured by Kureha Co., Ltd.) as a binder (volume ratio 100:25:6:3) are added to a dispersion medium and mixed using an ultrasonic homogenizer to obtain a positive electrode composite slurry. The obtained slurry is then coated onto an aluminum foil serving as the positive electrode current collector layer using a doctor blade, and the dispersion medium is dried and removed. This yields a positive electrode laminate with a positive electrode active material layer formed on the positive electrode current collector layer.
[0187] <Fabrication of Solid Electrolyte Layer>
[0188] At 1cm 2 100 mg of solid electrolyte is placed in a barrel made by Macor and pressed with a pressure of 100 MPa to create a solid electrolyte layer.
[0189] <Battery Making>
[0190] A negative electrode stack is disposed on one surface of the solid electrolyte layer with the negative electrode active material layers facing each other, and pressed under a pressure of 100 MPa. Then, a positive electrode stack is disposed on the other surface of the solid electrolyte layer with the positive electrode active material layers facing each other, and pressed under a pressure of 500 MPa. Thus, the all-solid-state battery of Example 1 is obtained.
[0191] <Determination of the Increase in Constraint Pressure>
[0192] The resulting battery was charged to 4.55V using a constant current-constant voltage (DCV) method at 0.245mA, and then discharged to 3.0V using the same DCV method at 0.245mA. During this charge-discharge cycle, the constraint voltage (MPa / mAh) was measured. The increase in constraint voltage was calculated by subtracting the initial constraint voltage from the constraint voltage at 4.55V. This increase in constraint voltage represents the expansion of the active material particles in the porous silicon electrode; a smaller value indicates a better result.
[0193] <<Examples 2-4 and Comparative Example 1>>
[0194] Except for changing the temperature and time during the reduction process as described in Table 1, all-solid-state batteries of Examples 2-4 and Comparative Example 1 were obtained in the same manner as in Example 1 and evaluated.
[0195] The evaluation results for each case are shown in Table 1 and Figure 3 In Table 1 and Figure 3 In Table 1, the increase in constraint pressure for Comparative Example 1 is set to 100, and the increase in constraint pressure for the other examples is shown as a relative value. Furthermore, in Table 1, "orifice diameter" and "support diameter" refer to "average orifice diameter" and "average support diameter," respectively.
[0196] [Table 1]
[0197]
[0198] As shown in Table 1 and Figure 3 As shown, in the battery of the embodiment containing porous silicon electrode active material particles with an average pore diameter of 8.0 or less relative to the average pillar diameter, the increase in confinement pressure is small.
Claims
1. Porous silicon electrode active material particles having multiple pores and pillars of a three-dimensional structure surrounding the multiple pores, wherein the ratio of the average pore diameter to the average pillar diameter is 8.0 or less.
2. The porous silicon electrode active material particles according to claim 1, wherein, The ratio is above 2.0 and below 7.
5.
3. The porous silicon electrode active material particles according to claim 2, wherein, The ratio is above 3.0 and below 6.
5.
4. The porous silicon electrode active material particles according to claim 1, wherein, The average pore diameter is above 20 nm and below 35 nm.
5. The porous silicon electrode active material particles according to claim 1, wherein, The average diameter of the support column is greater than 1 nm and less than 15 nm.
6. The porous silicon electrode active material particles according to claim 1, wherein, The porosity of the cross-sectional SEM image is above 30% and below 55% of the area.
7. An electrode composite material comprising porous silicon electrode active material particles according to any one of claims 1 to 6.
8. A battery having, in sequence, a negative electrode active material layer, an electrolyte layer, and a positive electrode active material layer, wherein the negative electrode active material layer comprises the electrode composite material according to claim 7.
9. The battery according to claim 8, wherein the electrolyte layer comprises a solid electrolyte.
10. A method for manufacturing porous silicon electrode active material particles according to any one of claims 1 to 6, comprising the following steps: (a) Reduction treatment of silica particles with magnesium at a temperature above 700°C and below 750°C yields precursor particles containing silicon and magnesium oxide; and (b) Remove the magnesium oxide from the precursor particles.
11. The method according to claim 10, wherein, In step (a), the silica particles are reduced with the magnesium for a period of 10 hours or more but less than 20 hours.
12. The method according to claim 10, wherein, In step (b), the magnesium oxide is removed by treating the precursor particles with acid.
Citation Information
Patent Citations
Negative electrode mixture layer
JP2020170605A